Synergistic Anti-arrhythmic Effects in Human Atria with Combined Use of Sodium Blockers and Acacetin - Ni, Haibo; Whittaker, Dominic G.; Wang, Wei; Giles, Wayne R.; Narayan, Sanjiv M.; Zhang, Henggui (Frontiers in Physiology, 2017)
Simultaneous block of both atrial-specific ultra-rapid delayed rectifier potassium (K+) current (IKur) and the Na+ current (INa) has been hypothesised to be anti-atrial fibrillation (AF), without inducing ventricular side effects. However, the advantage of simultaneously blocking these two channels in AF remains to be documented. IKur blockers such as acacetin and AVE0118, partially inhibit other K+ currents in the atria. Whether this multi-K+-block produces greater anti-AF effects compared with selective IKur-block has not been fully understood. The aim of this study was to computationally i) assess the impact of multi-K+-block as exhibited by many IKur blockers, and ii) evaluate the antiarrhythmic effect of blocking IKur and INa, either alone or in combination, on atrial and ventricular excitation. Human atrial and ventricular cell models were modified to incorporate dose-dependent actions of acacetin (a multichannel blocker primarily inhibiting IKur while less potently blocking Ito, IKr and IKs). Rate- and atrial-selective inhibition of INa was also considered. These single myocyte models were then incorporated into 2D and 3D models of the human atria. Blocking IKur produced pronounced action potential duration (APD) prolongation in atrial myocytes. Combined multiple K+-channel block of acacetin exhibited synergistic APD prolongations. Synergistically anti-AF effects of INa and combined IKur/K+-channel blocking were also observed. The attainable maximal AF-selectivity of INa inhibition was greatly augmented by blocking IKur or multiple K+-currents in the atrial myocytes. This enhanced anti-arrhythmic effects of combined block of Na+¬¬- and K+-channels were also seen in 2D and 3D simulations; specially, there was an enhanced efficacy in terminating re-entrant excitation waves. However, in the human ventricular myocytes and tissue, cellular repolarisation and computed QT intervals were modestly affected. In conclusion, this study demonstrates synergistic antiarrhythmic benefits of combined block of IKur and INa, as well as those of INa and combined multi K+-current block of acacetin, without significant alterations of ventricular repolarisation and QT intervals. This approach may be a valuable strategy for the treatment of AF.